2014
DOI: 10.1186/2047-783x-19-26
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-ERCP pancreatitis: a systematic review of clinical trials with a large sample size in the past 10 years

Abstract: BackgroundPost- endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) is the most common and most severe complication associated with diagnostic and therapeutic ERCP. A multivariate analysis of risk factors for PEP is essential for identifying patients at high risk and subsequently choosing other suitable diagnoses.MethodsPertinent publications were identified through systematic searches of MEDLINE, Elsevier, and Springer; we performed a systematic review of 12 clinical studies published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 30 publications
5
61
0
3
Order By: Relevance
“…PEP is associated with higher morbidity and mortality beside its effect in increasing the consumption of hospital resources[11]. Identification of clinical and procedural correlates for PEP is of crucial importance in the practice of ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…PEP is associated with higher morbidity and mortality beside its effect in increasing the consumption of hospital resources[11]. Identification of clinical and procedural correlates for PEP is of crucial importance in the practice of ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory subgroup analysis by calculating relative risks was performed for pre-specified factors which conveyed a higher risk for PEP - pancreatic stent placement, suspected sphincter of Oddi dysfunction, history of PEP, difficult cannulation, wire cannulation of the pancreatic duct, pancreatography, pancreatic acinarization, therapeutic biliary sphincterotomy, therapeutic pancreatic sphincterotomy, balloon dilation of the biliary sphincter, and trainee involvement in the ERCP. 13 …”
Section: Methodsmentioning
confidence: 99%
“…They reported that pancreatic injection (OR 2.2, 95% CI 1.6-3.01, p < 0.001) was one of the risk factors for PEP as an endoscopy-related factor. In addition, procedures associated with difficult selective cannulation have been confirmed as risk factors for PEP in other studies [20,21]. Further, various efforts to prevent PEP have been reported.…”
Section: Discussionmentioning
confidence: 78%